2019
DOI: 10.3389/fpsyg.2018.02777
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious Motives and Actions – Agency, Freedom and Responsibility

Abstract: According to many criteria, agency, intentionality, responsibility and freedom of decision, require conscious decisions. Freud already assumed that many of our decisions are influenced by dynamically unconscious motives or that we even perform unconscious actions based on completely unconscious considerations. Such actions might not be intentional, and perhaps not even actions in the narrow sense, we would not be responsible for them and freedom of decision would be missing. Recent psychological and neurophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Moreover, Lumer (2019) has suggested that the folk conception is also aligned with psychological theories focused on describing the mechanisms that underpin intention and action, which are in turn closer to the conceptualization of free will as free action. Lumer (2019) refers to the psychological theories as intentional-causalist models, and examples of these include Social learning theory- Bandura (2001); Reactance theory- Brehm and Brehm (1981); Self-determination theory- Deci and Ryan (2012); Intention-action theory- Haggard (2017); Rubicon model of action phases- Achtziger and Gollwitzer (2018) and Heckhausen & Gollwitzer (1987); Dynamic monitoring and control theory- Osman (2010Osman ( , 2014. These theoretical models outline psychological experience that can be used to identify that an action is free.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Lumer (2019) has suggested that the folk conception is also aligned with psychological theories focused on describing the mechanisms that underpin intention and action, which are in turn closer to the conceptualization of free will as free action. Lumer (2019) refers to the psychological theories as intentional-causalist models, and examples of these include Social learning theory- Bandura (2001); Reactance theory- Brehm and Brehm (1981); Self-determination theory- Deci and Ryan (2012); Intention-action theory- Haggard (2017); Rubicon model of action phases- Achtziger and Gollwitzer (2018) and Heckhausen & Gollwitzer (1987); Dynamic monitoring and control theory- Osman (2010Osman ( , 2014. These theoretical models outline psychological experience that can be used to identify that an action is free.…”
mentioning
confidence: 99%
“…Irrespective of whether or not humans ultimately possess free will, as mentioned, public conceptions of free will have been characterized as more closely associated with free action (e.g., Monroe & Malle, 2010;Shepherd, 2015;Stillman et al, 2011). Moreover, Lumer (2019) has suggested that the folk conception is also aligned with psychological theories focused on describing the mechanisms that underpin intention and action, which are in turn closer to the conceptualization of free will as free action. Lumer (2019) refers to the psychological theories as intentional-causalist models, and examples of these include Social learning theory- Bandura (2001); Reactance theory- Brehm and Brehm (1981); Self-determination theory- Deci and Ryan (2012); Intention-action theory- Haggard (2017); Rubicon model of action phases- Achtziger and Gollwitzer (2018) and Heckhausen & Gollwitzer (1987); Dynamic monitoring and control theory- Osman (2010Osman ( , 2014.…”
mentioning
confidence: 99%
“…Individual unconscious influences on behavior have been discussed together with concepts of intentionality, agency, responsibility, and compatibility of freedom of decision[ 52 - 55 ]. The analysis of expressions, behavior, and other enactments as an unbiased expression of intentionality is seen as problematic in psychoanalysis; consciousness is a necessary precondition for a sense of agency, intentionality, and freedom.…”
Section: Discussionmentioning
confidence: 99%
“…Psychologists have found that there are many behaviors that an individual takes up without being aware of the motivation behind them, such as automatic behavior, habitualized behavior, unconscious actions, etc. (Lumer, 2019).…”
Section: Motives and Behavior Behind Using Facebook*mentioning
confidence: 99%